Public support for better controls on lobbying and industry influence in Aotearoa New Zealand: findings from a national survey - Emma Shields; Andrew Gray; Rose Crossin; Calvin Cochran; Louise Signal; Ella Iosua; Rana Peniamina; Bronwen McNoe (New Zealand Medical Journal, 2026)
aim: Effective cancer prevention relies on policy and regulatory environments that limit population exposure to carcinogenic risks, including harmful commodities. In Aotearoa New Zealand, limited regulation of industry influence on health policy has contributed to persistent cancer inequities, particularly for Māori. This study assessed public support for controls on lobbying and industry influence in Aotearoa New Zealand, both generally and specifically relating to unhealthy food and alcohol. methods: A panel-based survey of adults in Aotearoa New Zealand assessed support for proposed lobbying regulations, specifically mandatory rules for lobbyists, cooling-off periods and excluding the alcohol and unhealthy food industries from public health policymaking. Results were weighted by age group, gender and Māori ethnicity, and examined overall and by gender, age, ethnicity and voting intention. results: We received 1,635 responses, which included 385 Māori (23.5%, unweighted) and 368 Pacific people (22.5%, unweighted) following oversampling of these groups who are of particular interest. There was strong public support for lobbying regulation measures. Support exceeded 60% across voters of all political parties. Mandatory rules for all lobbyists received the highest support, with over 80% support among voters for each political party and undecided voters. More than 70% overall supported excluding alcohol and unhealthy food industries from health policymaking. conclusion: There is strong public support for regulating lobbying, indicating a clear public mandate to protect cancer-related policies from vested and commercial interests through strengthened lobbying controls.